The mediating effect of service quality on the relationship between logistics resources and sustainable competitive advantage in Iraqi Kurdistan hotels - Mohammed Abdul-Aziz Ahmad; Juraifa Jais (Cogent Business & Management, 2024)
Logistics resources play a critical role in shaping service quality and maintaining organizational competitiveness. This study examines how service quality (SQ) and logistics resources (LR) affect the sustainable competitive advantage (SCA) of hotels in Kurdistan, Iraq. Importantly, this study addresses a limited body of research in the Middle East, contributing a unique viewpoint on the relationship between logistics resources and service quality dynamics in the region. A questionnaire was employed to gather data from 152 hotel managers in Kurdistan, Iraq. The results indicate that sustainable competitive advantage was influenced by both the direct and indirect effects of service quality. When considering the role of service quality as a mediator, it was identified that it had a partial mediation effect on the relationship between logistics resources and sustainable competitive advantage. The findings provide an opportunity for practitioners to gain clear knowledge on the mediating effect of service quality between logistics resources and sustainable competitive advantage in the hotel industry. It can assist hotel managers in the region in focusing on and developing their service levels, particularly empathy, tangibles, reliability, responsiveness, and sensory, to achieve a sustainable competitive advantage. Furthermore, the study will provide benefits for the relevant authorities to emphasize strategic policy.
Keywords: 650; logistics resources; service quality; sustainable competitive advantage; hotel managers